Kelimpahan dan Keanekaragaman Jenis Ikan di Perairan Ndalir Kabupaten Merauke, Papua - Saleky, Dandi; Weremba, Efraim; Welikken, Marius A. (Politeknik Negeri Sambas, 2021)
This study aims to analyze the diversity of fish species caught on the Ndalir Coast of Merauke Regency. This research was conducted in Juli-August of 2020. The determination of the sampling points at the research location used the purposive random sampling method with two observation stations. Analysis of the research data using relative abundance (Kr), Shannon-Wienner index (H'), uniformity index (E), and dominance index (C), The number of fish catches during the study time was 431 which were divided into 12 species of fish. Station two has a greater number of catches than station one. The highest relative abundance was tongue fish (Cynoglossus abbreviation) (Station I) and mullet (Mugil cephalus) (Station II). The diversity index value at the two observation stations is in the medium category. The uniformity and dominance index values ​​show that the species at the two research stations are evenly distributed with no dominating species.